Rituximab, Methotrexate, Carmustine, Etoposide, and Prednisone (RMBVP) for the treatment of relapsed/refractory primary central nervous system lymphoma: a retrospective single-center study. Issue 3 (23rd February 2022) - Reiss, Samantha N.; Yerram, Prakirthi; Modelevsky, Lisa; Grommes, Christian
Abstract: Relapsed/refractory Primary Central Nervous System Lymphoma (R/R PCNSL) has a poor prognosis with no established preferred treatment. We report the efficacy and toxicity of a combination chemotherapy regimen: methotrexate, carmustine, etoposide, and prednisone with or without rituximab (RMBVP). This retrospective study included thirty patients who received a median of two 28-day cycles (0.5–5). The median age was 66 years (23–81); median KPS was 70 (30–90); 14 (46.7%) were women. Patients received a median of 2 prior lines of therapy and all received prior methotrexate. Of 29 evaluable patients, the overall response rate was 73.3% ( n  = 22). Median progression-free survival (PFS) was 15.6 months. Patients who recurred or progressed <12 months since last chemotherapy had a shorter median PFS (7.6 vs 37.6 months). Toxicity was moderate with 20% rates of severe myelosuppression. RMBVP is a tolerable treatment option for R/R PCNSL, with favorable response rates in those with recurrent disease.